1995
DOI: 10.1016/0014-5793(95)00338-a
|View full text |Cite
|
Sign up to set email alerts
|

A new function of Nm23/NDP kinase as a differentiation inhibitory factor, which does not require it's kinase activity

Abstract: We recently identified a differentiation inhibiting factor (I-factor) in mouse myeloid leukemia M1 cells as a murine homolog of nm23-H21nucleoside diphosphate kinase (NDPK)-B gene product. We examined the I-factor activities of several authentic nm231NDPK proteins, i.e recombinant rat NDPK a and t, recombinant mouse nm23-M1 and -M2, and recombinant human nm23-H1 and -H2 containing a mutant nm23-H2 his protein lacing NDPK activity. Almost all these nm23/NDPK proteins showed I-factor activity. Moreover, to under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 29 publications
0
36
0
1
Order By: Relevance
“…Earlier reports identified NDPK-B as a differentiation-inhibitory factor, which is able to inhibit the differentiation of several hematopoietic cell lines in vitro, where the inhibition was independent of the phosphotranferase activity, as demonstrated with NDPK-B mutants lacking the enzymatic activity (14,49). Moreover, several hematopoietic tumor cell lines stained positive for NDPK-B in flow cytometric analysis (50), and upregulation of the human NDPK-B gene was also observed in normal lymphocytes induced to proliferate with phytohemagglutinin (51).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Earlier reports identified NDPK-B as a differentiation-inhibitory factor, which is able to inhibit the differentiation of several hematopoietic cell lines in vitro, where the inhibition was independent of the phosphotranferase activity, as demonstrated with NDPK-B mutants lacking the enzymatic activity (14,49). Moreover, several hematopoietic tumor cell lines stained positive for NDPK-B in flow cytometric analysis (50), and upregulation of the human NDPK-B gene was also observed in normal lymphocytes induced to proliferate with phytohemagglutinin (51).…”
Section: Discussionmentioning
confidence: 87%
“…NDPKs were originally identified as essential housekeeping enzymes required for the synthesis of nucleoside triphosphates by catalyzing the transfer of the ␥-phosphoryl groups from nucleoside triphosphates to nucleoside diphosphates via a phosphohistidine 118 enzyme intermediate, and they play a role in maintaining intracellular nucleotide concentrations (10). Altered expression of NDPK is also reportedly involved in many cellular processes, including oncogenesis (11,12), cellular proliferation (13), differentiation (14,15), motility (16), development (17), DNA repair (18), and apoptosis (19). In Escherichia coli, NDPK functions as a mutator gene and is not essential for viability (20).…”
mentioning
confidence: 99%
“…We previously found that a differentiation inhibitory factor (I-factor) purified from a differentiation-resistant mouse myelogenous leukemia cell line was identical to nm23 protein. 1 Recently, we established an enzyme-linked immunosorbent assay (ELISA) technique of determining the serum level of nm23-H1 protein, 2 and reported that the level in patients with aggressive lymphoma was significantly higher than that in healthy individuals. Furthermore, this assay system can be useful to determine the therapeutic strategy for aggressive lymphoma since the prognosis is worse in patients with a high nm23-H1 level.…”
Section: To the Editormentioning
confidence: 99%
“…19,24 The measurements were made at the Department of Immunology, SRL, Tokyo, Japan. Soluble IL-2R was measured by sandwich ELISA as described in the literature.…”
Section: Elisa For Human Nm23-h1mentioning
confidence: 99%